Variations of Near Surface Energy Balance Caused by Land Cover Changes in the Semiarid Grassland Area of China - Qun’ou Jiang; Chengcai Tang; Enjun Ma; Yongwei Yuan; Wei Zhang (Advances in Meteorology, 2014)
This study applies the Dynamics of Land System (DLS) model to simulating the land cover under the designed scenarios and then analyzes the effects of land cover conversion on energy flux in the semiarid grassland area of China with the Weather Research and Forecasting (WRF) model. The results indicate that the grassland will show a steadily upgrowing trend under the coordinated environmental sustainability (CES) scenario. Compared to the CES scenario, the rate of increase in grassland cover is lower, while the rate of increase in urban land cover will be higher under the rapid economic growth (REG) scenario. Although the conversion from cropland to grassland will reduce the energy flux, the expansion of urban area and decreasing of forestry area will bring about more energy flux. As a whole, the energy flux of near surface will obviously not change under the CES scenario, and the climate therefore will not be possible to be influenced greatly by land cover change. The energy flux under the REG scenario is higher than that under the CES scenario. Those research conclusions can offer valuable information for the land use planning and climate change adaptation in the semiarid grassland area of China.